Efektivitas Ekstrak Etanol Daun Sirsak (Annona muricata Linn) dalam Mencegah Displasia Dorsum Lingue Tikus Galur Sprague Dawley yang Diinduksi 7,12 Dimetilbenz(Α)Antrasena - Prihatiningsih, Tyas; Haniastuti, Tetiana; Agustina, Dewi (e-GiGi, 2021)
Abstract: Polycyclic aromatic hydrocarbons (PAH) is one of the largest group of carcinogen in the environment.  An agent that has antigenotoxic and anticarcinogen potency is needed to prevent DNA damage and carcinogenesis. Soursop leaves have a chemopreventive action. This study was aimed to assess the effectiveness of ethanolic extract of soursop leaves in prevention of dysplasia of upper surface of tongue in rats. This was a true laboratory experimental study with the post test-only control group design, using 24 male Sprague Dawley rats divided into six groups. The upper surfaces of tongues of group I-III were induced by DMBA topically three times a week for 16 weeks; group II and III were induced by DMBA added soursop leaves ethanolic extract of 100 and 200 mg/kg body weight daily for 18 weeks; group IV was given soursop leaves ethanolic extract 200 mg/kg body weight; group V was given DMSO 1%; and group VI was untreated. After 18th week, rats were terminated and tongue necropsies in longitudinal anteroposterior direction were conducted. The clinical changes of the upper surfaces of the tongues were observed and the histological changes were observed by using HE staining to confirm signs of dysplasia. The Kruskal Wallis test showed differences between groups, and the Mann-Withney test showed not significantly decrease of mild dysplasia of group II and group III compared to group I (p>0.05). In conclusion, ethanolic extract of soursop leaves was not effective in prevention of dysplasia of the upper surface of rat’s tongue.Keywords: dysplasia; soursop leave extract; dorsal part of tongue; DMBA  Abstrak: Senyawa golongan PAH merupakan salah satu kelompok karsinogen terbesar di lingkungan. Sebagai upaya untuk mencegah kerusakan DNA serta karsinogenesis, diperlukan suatu agen yang berpotensi antigenotoksik sekaligus antikarsinogenik. Daun sirsak terbukti mempunyai aksi kemopreventif. Penelitian ini bertujuan untuk mengkaji efektivitas ekstrak etanol daun sirsak dalam mencegah displasia pada dorsum lingue tikus. Jenis penelitian ialah true experimental laboratory dengan the post test-only control group design yang menggunakan 24 ekor tikus galur Sprague Dawley jantan, dibagi dalam enam kelompok. Dorsum lingue tikus kelompok I - III diinduksi DMBA secara topikal tiga kali seminggu selama 16 minggu; kelompok II dan III selain diinduksi DMBA, juga diberi ekstrak etanol daun sirsak 100 dan 200 mg/kg berat badan setiap hari selama 18 minggu; kelompok IV diberi ekstrak etanol 200 mg/kg BB; kelompok V diberi DMSO 1%; dan kelompok VI tidak diberi perlakuan. Terminasi dan nekropsi lidah tikus longitudinal anteroposterior dilaksanakan setelah minggu ke 18. Perubahan pada dorsum lingue diamati secara klinis dan perubahan histologik dilihat dengan pewarnaan HE untuk mengonfirmasi tanda displasia. Uji Kruskal Wallis menunjukkan perbedaan antar kelompok, sedangkan uji Mann Whitney menunjukkan penurunan tidak bermakna displasia ringan pada kelompok II dan III dibanding kelompok I. Simpulan penelitian ini ialah ekstrak etanol daun sirsak tidak efektif dalam mencegah displasia epitel dorsum lingue tikus.Kata kunci: displasia; ekstrak daun sirsak; dorsum lingue; DMBA